2021
DOI: 10.3389/fphar.2021.628651
|View full text |Cite
|
Sign up to set email alerts
|

Hypericum perforatum L. Regulates Glutathione Redox Stress and Normalizes Ggt1/Anpep Signaling to Alleviate OVX-Induced Kidney Dysfunction

Abstract: Menopause and associated renal complications are linked to systemic redox stress, and the causal factors remain unclear. As the role of Hypericum perforatum L. (HPL) in menopause-induced kidney disease therapy is still ambiguous, we aim to explore the effects of HPL on systemic redox stress under ovariectomy (OVX)-induced kidney dysfunction conditions. Here, using combined proteomic and metabolomic approaches, we constructed a multi-scaled “HPL-disease-gene-metabolite” network to generate a therapeutic “big pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 70 publications
1
1
0
Order By: Relevance
“…As a result, Fmo5 and Ggt1 immunostaining was present in normal renal tubular (CT group) in a perinuclear pattern and was localized mainly to tubular epithelial cells (Additional file 1: Fig. S4A and C), which is consistent with previous studies that Fmo5 are primarily localized to the distal tubules of the cortex, proximal tubules and the collecting ducts of the medulla [20], and Ggt1 is expressed at high levels in renal proximal tubules [21]. Then, we found that immunostaining for Fmo5 and Ggt1 confirmed the proteomics data (Fig.…”
Section: Effects Of Ant On the Metabolism Expression Profile Of Db/ D...supporting
confidence: 90%
“…As a result, Fmo5 and Ggt1 immunostaining was present in normal renal tubular (CT group) in a perinuclear pattern and was localized mainly to tubular epithelial cells (Additional file 1: Fig. S4A and C), which is consistent with previous studies that Fmo5 are primarily localized to the distal tubules of the cortex, proximal tubules and the collecting ducts of the medulla [20], and Ggt1 is expressed at high levels in renal proximal tubules [21]. Then, we found that immunostaining for Fmo5 and Ggt1 confirmed the proteomics data (Fig.…”
Section: Effects Of Ant On the Metabolism Expression Profile Of Db/ D...supporting
confidence: 90%
“…These endotoxins can activate TLR4-mediated reactions, including initiation of the NF-κB signaling pathway ( Tang et al, 2021 ). NF-κB is a major transcription factor involved in inflammatory diseases, which can respond to heat-stress stimuli and activate the NF-κB signaling pathway in broilers ( Xu et al, 2023 ), thereby inducing tissue damage ( Liu W. C. et al, 2021 ; Liu Y. R. et al, 2021 ). NF-κB acts downstream of TLR4 and other immune receptors, increasing the excessive production of IL-6, IL-1β, and TNF-α leads to the occurrence of inflammatory responses in response to heat stress ( Vallabhapurapu and Karin, 2009 ).…”
Section: Discussionmentioning
confidence: 99%